2011
DOI: 10.1002/ibd.21605
|View full text |Cite
|
Sign up to set email alerts
|

Prednisolone treatment affects the performance of the QuantiFERON gold in-tube test and the tuberculin skin test in patients with autoimmune disorders screened for latent tuberculosis infection

Abstract: Oral prednisolone severely suppressed QFT-IT and TST performance, whereas the long-acting corticosteroids methotrexate, azathioprine, and 5-ASA did not have a similar detrimental effect. Patients should be screened for LTBI with QFT-IT or TST prior to initiation of prednisolone therapy and negative QFT-IT or TST results interpreted with caution in patients treated with any corticosteroid until further data are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 40 publications
7
77
2
4
Order By: Relevance
“…However, false-negative IGRA results occur, and test performance is impaired, in patients treated with prednisolone and possibly also other drugs used to treat inflammatory diseases [77].…”
Section: Immunosuppressive Therapymentioning
confidence: 99%
“…However, false-negative IGRA results occur, and test performance is impaired, in patients treated with prednisolone and possibly also other drugs used to treat inflammatory diseases [77].…”
Section: Immunosuppressive Therapymentioning
confidence: 99%
“…In terms of investigations of factors correlating with indeterminate test rates, Belard et al evaluated the performance of IGRA in patients with CID and found an indeterminate rate of 5% with the observation that .10 mg/day of prednisolone was associated with a 27% risk of indeterminate results (10). These investigators also examined the quantitative effect of different treatment regimens on IFNg response after mitogen stimulation and found that GC use was associated with a reduced median IFNg response and this effect was dose-dependent (10). In a large study of the performance of multiple screening tests in Asian patients with rheumatoid arthritis and ankylosing spondylitis, Hsia et al found no correlations with GCs or DMARDs (20).…”
Section: Discussionmentioning
confidence: 99%
“…Indeterminate results generally lead clinicians to repeat IGRA or TST testing or to rely on other clinical and radiologic factors to help interpret the test result. While it has been recognized that indeterminate results occur more frequently in patients with autoimmune diseases, no useful predictors have been identified (10)(11)(12)(13). The objective of this study is to assess the rate of indeterminate results in patients with concurrent immunosuppressive therapy in an attempt to assist clinicians in test selection, timing, and interpretation and to identify factors associated with indeterminate test results.…”
Section: Introductionmentioning
confidence: 99%
“…En pacientes que reciben estos compuestos, especialmente en combinación, el porcentaje de pruebas indeterminadas se acerca a 30%, 10 veces superior a lo observado en la población general 91,92 . La probabilidad de una prueba indeterminada es mayor si el paciente recibe > 10 a 15 mg diarios de dosis equivalente de prednisona 92,93 . Los corticosteroides también tornan negativa la prueba de tuberculina 93 .…”
Section: Evaluación Del Riesgo De Tuberculosis Y Su Prevenciónunclassified
“…La probabilidad de una prueba indeterminada es mayor si el paciente recibe > 10 a 15 mg diarios de dosis equivalente de prednisona 92,93 . Los corticosteroides también tornan negativa la prueba de tuberculina 93 .…”
Section: Evaluación Del Riesgo De Tuberculosis Y Su Prevenciónunclassified